Memories of formation: senses and sensibilities during the beginning of religious life in Congregação das Irmãzinhas da Imaculada Conceição (1960 – 1990) (Tempo e Argumento, 2010)
The  aim of this paper is to study different aspects of female religious training  from the perspective of the sensibilities and discipline. For this we present  testimony from women who went through the training process in the CIIC. The  statements put together with the dialogue and with the training manuals build a  rather large scenario, which offers an insight into the construction of meaning  and vocations to the later work institutionally linked to the Catholic Church.
Keywords: religious life; formation; discipline; memory